6-Methoxydihydroavicine is a benzophenanthridine alkaloid with anti-leukemia activity - Yang, Yingying; Spagnuolo, Paul A. (Frontiers in Pharmacology, 2025)
BackgroundAcute myeloid leukemia (AML) is an aggressive hematological malignancy with limited therapeutic options. Despite recent advances in targeted therapies, patients are still faced with poor survival outcomes. Thus, development of novel therapeutic agents with broad efficacy remains an urgent need.MethodsWe conducted a natural compound library screen and identified 6-methoxydihydroavicine, a plant-derived benzophenanthridine alkaloid (BPA) derived from the genus of Macleaya - a perennial herb found in China, North America and Europe - as a potent compound that reduced AML cell viability. We evaluated its cytotoxicity in multiple AML cell lines and investigated its underlying mechanism of action using assays that probed mitochondrial function, and reactive oxygen species (ROS) production.Results6-methoxydihydroavicine significantly reduced cell viability and induced caspase-mediated cell death in AML cell lines in a dose-dependent manner. Mechanistically, 6-methoxydihydroavicine triggered accumulation of mitochondrial ROS and disrupted electron transport chain (ETC) function.ConclusionOur findings demonstrate that 6-methoxydihydroavicine exerts strong cytotoxic effects against AML cells through mitochondrial dysfunction and ROS-mediated apoptosis. As a natural, plant-derived compound with distinct anti-AML properties, 6-methoxydihydroavicine represents a promising candidate for further development as a therapeutic agent for AML.